Randomized clinical trial on the survival of lithium disilicate posterior partial restorations bonded using immediate or delayed dentin sealing after 3 years of function. (June 2019) - van den Breemer, C.R.G.; Cune, M.S.; Özcan, M.; Naves, L.Z.; Kerdijk, W.; Gresnigt, M.M.M.
Abstract: Objectives: The survival and success rate and the quality of survival of partial ceramic restorations bonded employing Immediate (IDS) or Delayed Dentin Sealing (DDS) in vital molar teeth were evaluated in a randomized clinical trial with within-subject comparison study. Materials and methods: 30 patients received two lithium disilicate ceramic (IPS-e.max press, Ivoclar Vivadent) partial restorations on vital first or second molar teeth (N = 60). The two teeth randomly received either IDS (test group, n = 30) or DDS (control group, n = 30). Partial ceramic restorations were luted (Variolink Ultra, Ivoclar Vivadent) two weeks after preparation. Evaluations were performed at 1 week, 12 months and 36 months post-operatively, using qualitative (FDI) criteria. Representative failures were evaluated microscopically (SEM) and by means of simplified qualitative fractography analysis. Results: One absolute failure occurred in the DDS group due to (secondary) caries. The overall survival rate according to Kaplan-Meier after 3 years was 98.3% (FDI criteria score 1–4, n = 59) and the overall success rate was 85% (FDI criteria score 1–3, n = 51), with no significant difference between restorations in the IDS and DDS group (p = 0.32; Kaplan-Meier, Log Rank (Mantel-Cox), CI = 95%). For the quality of the survival, no statistically significant differences were found between IDS and DDS (p = 0.7; Kaplan-Meier, Log Rank (Mantel-Cox), CI = 95%) restorations on any follow-up timepoints for any of the FDI criteria (Wilcoxon, McNemar, p > 0.05). Conclusion: Adhesively luted partial ceramic restorations in vital molar teeth have a good prognosis, however IDS did not show any differences in success and survival rates after 3 years of function.